Analysis of Priority Strategies for Developing Religious Tourism of The Sunan Gunung Jati Cemetry Using The Carl Method - Bakhri, Syaeful; Maemunah, Maemunah; Anggraeni, Devina; Maulana, Saptaji; Azizah, Imroatul; Nurfarikhah, Ika; Jannah, Isroqtul (Indonesian Journal of Islamic Business and Economics (IJIBE), 2024)
The development of tourism cannot be denied, as does the majority of Muslims. Most Muslim communities make religious tourism increasingly popular, so research must be done to accommodate this. This research aims to analyze and provide new concepts related to priority development strategies that are needed and can contribute to the development of religious tourism at the Sunan Gunung Jati Tomb. The research method in this research is descriptive qualitative. The qualitative data obtained is then processed by giving weights and numbers to produce quantitative data using the CARL method to determine the priority scale in solving a problem. The big priority problem is limited human resources, which are not balanced with the number of tourists who come, so tourists cannot experience maximum service; the local community has not entirely played a role in business activities in the Sunan Gunung Jati cemetery tourist area, lack of supporting facilities and infrastructure such as lack of land. To open a business. There are minor problems, namely the public's understanding of sales procedures, the facilities for burial buildings located in residential areas are challenging to develop, and the geographical location close to the sea causes hot weather, reducing tourists visiting.